(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
Notariado y construcción social de la realidad, II: los registros notariales medievales (NotFor II) is a three-year research project (from 01/09/2024 to 31/12/2027) which aims to study notaries public and the issuing of their charters as an essential component in the development of late medieval written culture. Its objectives are the identification and edition of medieval notarial registers; the study of their expedition, form, use and preservation; and the attempt to understand them from a European perspective, moving toward a general understanding of these books.